lllness behaviour in elite middle and long distance runners - Currie, A.; Potts, S. G.; Donovan, W.; Blackwood, D. (British Journal of Sports Medicine, 1999)
OBJECTIVES: To examine the illness attitudes and beliefs known to be associated with abnormal illness behaviour (where symptoms are present in excess of objective signs and pathology) in elite middle and long distance runners, in comparison with non-athlete controls. METHODS: A total of 150 athletes were surveyed using the illness behaviour questionnaire as an instrument to explore the psychological attributes associated with abnormal illness behaviour. Subjects also completed the general health questionnaire as a measure of psychiatric morbidity. A control group of 150 subjects, matched for age, sex, and social class, were surveyed using the same instruments. RESULTS: A multivariate analysis of illness behaviour questionnaire responses showed that the athletes' group differed significantly from the control group (Hotelling's T: Exact F = 2.68; p = 0.01). In particular, athletes were more somatically focused (difference between means -0.27; 95% confidence interval -0.50 to -0.03) and more likely to deny the impact of stresses in their life (difference between means 0.78; 95% confidence interval 0.31 to 1.25). Athletes were also higher scorers on the Whiteley Index of Hypochondriasis (difference between means 0.76; 95% confidence interval 0.04 to 1.48). There were no differences in the levels of psychiatric morbidity between the two groups. CONCLUSIONS: The illness attitudes and beliefs of athletes differ from those of a well matched control population. The origin of these psychological attributes is not clear but those who treat athletes need to be aware of them.